2021
DOI: 10.1101/2021.03.19.21251426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T-cell receptor sequencing identifies prior SARS-CoV-2 infection and correlates with neutralizing antibody titers and disease severity

Abstract: Measuring the adaptive immune response to SARS-CoV-2 can enable the assessment of past infection as well as protective immunity and the risk of reinfection. While neutralizing antibody (nAb) titers are one measure of protection, such assays are challenging to perform at a large scale and the longevity of the SARS-CoV-2 nAb response is not fully understood. Here, we apply a T-cell receptor (TCR) sequencing assay that can be performed on a small volume standard blood sample to assess the adaptive T-cell response… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 42 publications
2
23
1
Order By: Relevance
“…When thinking about the potential impact of MS DMTs on vaccine efficacy, the role of specific immune cell populations may be considered. For example, T cell signatures may be a more sensitive measure of past SARS-CoV-2 infection than antibody assays, as individuals with symptomatic infections or who required hospitalization had higher T cell responses [ 176 ]. This suggests that disease-specific memory T cells, in addition to antibody titers, may be measurable and reliable correlates of protection [ 176 ].…”
Section: Covid-19 Vaccine Trials and Considerations For People With Msmentioning
confidence: 99%
See 2 more Smart Citations
“…When thinking about the potential impact of MS DMTs on vaccine efficacy, the role of specific immune cell populations may be considered. For example, T cell signatures may be a more sensitive measure of past SARS-CoV-2 infection than antibody assays, as individuals with symptomatic infections or who required hospitalization had higher T cell responses [ 176 ]. This suggests that disease-specific memory T cells, in addition to antibody titers, may be measurable and reliable correlates of protection [ 176 ].…”
Section: Covid-19 Vaccine Trials and Considerations For People With Msmentioning
confidence: 99%
“…For example, T cell signatures may be a more sensitive measure of past SARS-CoV-2 infection than antibody assays, as individuals with symptomatic infections or who required hospitalization had higher T cell responses [ 176 ]. This suggests that disease-specific memory T cells, in addition to antibody titers, may be measurable and reliable correlates of protection [ 176 ]. However, SARS-CoV-2-reactive CD4 + T cells have been reported in 35–60% of unexposed individuals, suggesting possible cross-reactive T cell recognition between other coronaviruses (e.g., common cold viruses) and COVID-19 [ 177 – 179 ]; the protective effect of such cross-reactive T cells is unclear.…”
Section: Covid-19 Vaccine Trials and Considerations For People With Msmentioning
confidence: 99%
See 1 more Smart Citation
“…CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) previous observations characterizing the T-cell response in patients infected with SARS-CoV-2 (46). Median model scores decreased from 6.1 to 2.5, and model sensitivity decreased from 56% (91/161) at enrollment to 32% (51/161) 6 months posttreatment.…”
Section: Disease-associated Tcrs and Seropositivity Wane After Treatmentmentioning
confidence: 79%
“…We have previously shown that classifiers based on quantification of disease-associated public TCR sequences can be used for sensitive identification of past infection with CMV (43) or SARS-CoV-2 (44). Such classifiers leverage the relative frequency of disease-associated sequences within the repertoire, measures that have been shown to be associated with disease severity in the setting of SARS-CoV-2 (45,46). Clinical validation of a T-cell assay for SARS-CoV-2 utilizing a similar methodology demonstrated high positive percent agreement (>94.5%) and negative percent agreement (~100%) with reverse transcriptase PCR (RT-PCR) for detection of past SARS-CoV-2 infection (46,47).…”
Section: Introductionmentioning
confidence: 99%